Sunshine Trading and Financial Market Equilibrium - Admanti, Anat R.; Pfleiderer, Paul (Review of Financial Studies, 1991)
In this article, we consider the possibility that some liquidity traders preannounce the size of their orders, a practice that has come to be known as “sunshine trading”. Two possible effects preannouncement might have on the equilibrium are examined. First, since it identifies certain trades as informationless, preannouncement changes the nature of any informational asymmetries in the market. Second, preannouncement can coordinate the supply and demand of liquidity in the market. We show that preannouncement typically reduces the trading costs of those who preannounce, but its effects on the trading costs and welfare of other traders are ambiguous. We also examine the implications of preannouncement for the distribution of prices and the amount of information that prices reveal.